INTRA-SPECIFIC VARIABILITY IN SESAME (SESAMUN INDICUM L.) FOR VARIOUS QUANTITATIVE AND QUALITATIVE ATTRIBUTES UNDER DIFFERENTIAL SALT REGIMES - Mahmood, Seema; Iram, Shazia; Athar, Habib-ur-Rehman (Journal of Research (Science), 2003)
Salt tolerance of four sesame cultivars; Faisalabad Black, Pb-90-93, Pb-T-90 and T-S-3 was assessed at germination and later growth stages. Seed germination and vegetative growth were evaluated in response to five salinity levels of NaCl and Na2SO4 while yield experiment was conducted using three concentrations of these salts. The cultivars differed in their sensitivities to these salts for germination and seedling development. T-S-3 emerged as a sensitive cultivar at the germination stage. Likewise, Pb-90-93 produced lower fresh and dry seedling biomass in response to salinity regimes. However, Faisalabad Black exhibited higher germination and produced greater dry biomass of seedlings. Plant height, leaf growth and flowering appeared to be sensitive parameters to salt stress. A considerable degree of variability was found between cultivars for quantitative and qualitative traits. In general, the responses of Pb-T- 90 and Pb-90-93 were intermediate while T-S-3 appeared to be more prone to salinity for yield attributes. Faisalabad Black sustained growth, yield and qualitative traits under varying salt regimes and revealed a consistent degree of salt tolerance with time course changes in growth. The study affirmed that individuals who can withstand prevailing stress at early growth stages could certainly produce tolerant adult plants.